Functional, cognitive and physical outcomes 3 years after minor lacunar or cortical ischaemic stroke. Issue 4 (15th December 2018) - McHutchison, Caroline A; Cvoro, Vera; Makin, Stephen; Chappell, Francesca M; Shuler, Kirsten; Wardlaw, Joanna M
Abstract : Objective: Many studies examining stroke outcomes focus on more severe strokes or have short follow-up periods, so the long-term outcomes post-minor ischaemic stroke are unclear. Methods: We recruited participants from inpatient and outpatient services with a lacunar or minor cortical ischaemic stroke (National Institutes of Health Stroke Scale score <8) and assessed current and premorbid cognitive functioning (Addenbrooke's Cognitive Examination–Revised (ACE-R), National Adult Reading Test (NART)), physical functioning (Timed Get Up and Go (TUG), 9-Hole Peg Test (9HPT)), dependency (modified Rankin Scale (mRS)), depression (Beck's Depression Inventory) in-person and remotely (Stroke Impact Scale). Results: We followed up 224/264 participants at 3 years (mean age at index stroke=67, 126 (56%) men, 25 non-contactable, 15 declined): 66/151 (44%) had cognitive impairment, mean ACE-R 88 (SD 9, range 54–100/100), 61/156 (39%) had depression and 26/223 (12%) were dependent (mRS=3–5). Cognitive impairment at 3 years affected all ACE-R subdomains and was associated with ACE-R 1 year (β=1.054, p<0.001) and NART (β=1.023, p<0.05). Poor physical function was associated with stroke severity (TUG, β=1.064, p<0.01) and recurrent stroke (9HPT, β=1.130, p<0.05 right, β=1.214, p<0.05 left). Higher ACE-R scores were associated with faster TUG (β=−0.279, p<0.05) and 9HPT (right β=−0.257, p<0.05; left β=−0.302, p=0.05) and inversely with dependency (mRS=3–5, OR 0.88, 95% CI 0.80 to 0.97). We adjusted analyses for demographic, stroke and known risk factors. In-person and remote assessments were highly correlated. Conclusions: Cognitive, physical impairments and depression are common and interrelated 3 years after minor stroke. Cognitive and physical impairments require rehabilitation after minor stroke and argue for better integration of stroke and dementia services.